689 Objective Assessment of Inpatient Sleep Patterns and Quality: A Pilot Study. (3rd May 2021) - Sussman, Sarah; Ananth, Ashwin; Fares, Elie; Boon, Maurits; Huntley, Colin; Fast, Zhanna
Abstract: Introduction: Sleep disruption is common among hospitalized patients due to psychological, physiological, and environmental reasons including illness, pain, anxiety, invasive interventions, frequent monitoring, and stimuli, especially noise and light. The AASM has published guidelines for the use of actigraphy in the outpatient setting, but there is a paucity of literature evaluating the validity of actigraphy in inpatients. The aim of this study is to evaluate sleep in hospitalized general medicine patients undergoing sleep medicine consultation using actigraphy and qualitative surveys. Methods: A single-site prospective study in hospitalized medicine patients. Patients were observed with a Fitbit® Charge3 wrist actigraphy device overnight, then administered 7 surveys: Richards-Campbell Sleep Questionnaire (RCSQ), qualitative questionnaires assessing sleep history, sleep hygiene, barriers to sleep, STOP-BANG, Epworth Sleepiness Scale (ESS), and Patient-Health Questionniare-2 (PHQ-2). Actigraphy data including total sleep time, slow wave sleep time, and number of awakenings was compared with patient-reported data. Results: In preliminary analysis, six patients met inclusion criteria and underwent sleep medicine consultation, overnight actigraphy, and completed 7 surveys. Based on subjective sleep history questionnaires, average total sleep time was 437 + 215 minutes. Actigraphy revealed average total sleep time was 228 + 80 minutes with an average of 3.6 nocturnal awakenings. Increased number of awakenings on actigraphy was not correlated with increased number of awakenings by survey. The most frequently reported barriers to sleep on patient surveys were pain and being woken up for labs or vital signs. The average STOP-BANG score was 6 out of 8 and average ESS was 14 out of 24. Conclusion: Restorative sleep warrants consideration alongside complex medical care during hospitalization. Patients experience decreased total sleep time and increased number of awakenings while in the hospital compared with their subjective estimates of sleep at home. Actigraphy provides a non-invasive and reliable way to monitor some sleep parameters in the inpatient setting. An elevated STOP-BANG score could represent sleep disordered breathing and impact perceptions of sleep quality. Patient-identified barriers to sleep are targets for quality improvement. Future studies should compare inpatient actigraphy data to polysomnographic data and the effect of sleep-directed interventions on sleep quality in the hospital. Support (if any):